Ag3PO4/TiO2‐assisted degradation of malachite green in aqueous solution treated by dielectric barrier discharge plasma. Issue 7 (17th November 2015) - Xin, Lu; Sun, Yabing; Feng, Jingwei
Abstract: BACKGROUND: A new method of malachite green (MG) degradation by dielectric barrier discharge (DBD) plasma with an Ag3 PO4 /TiO2 composite photocatalyst was investigated. Ag3 PO4 /TiO2 was synthetized by an in situ precipitation method under room conditions, and analyzed by XRD, SEM, TEM, XRF and BET. The catalytic activity, the reaction mechanisms, the intermediates of MG degradation and the proposed degradation pathways were also evaluated. RESULT: The efficiency of degradation of 150 mL of MG with initial concentration 150 mg L −1 was improved from 80.9% to 94.2% in 14 min at input power of 80 W relative to the Ag3 PO4 /TiO2 cooperated as 0.05 g. Meanwhile, the TOC removal rate increased from 13.9% to 20.6%. CONCLUSIONS: It was shown that a synergistic effect existed between DBD plasma and Ag3 PO4 /TiO2 in the process of MG degradation. Higher input power, larger initial concentration and narrower air‐gap distance caused Ag3 PO4 /TiO2 to show even better effects in the DBD system, improving degradation efficiency and energy yield. Possible MG degradation pathways involved a series of deamination, denitrosation, demethylation, hydroxylation and oxidative openings of the aromatic ring processes. The study proposed an efficient technology and degradation mechanisms for MG wastewater treatment. © 2015 Society of Chemical Industry